(3x+4)^3=2197 solve this equation

Answers

Answer 1
Answer: (3x + 4)³ = 2197

Taking the cube root in this case is easier, although we can do it the extended way which is complicated.

\sqrt[3]{(3x+4)^3}\sqrt[3]{2197}
3x + 4 = 13

Now solve normally.

subtract 4
3x + 4 = 13
       -4    -4

3x = 9
Divide by 3 to isolate 3

(3x)/(3) = (9)/(3)
3 and 3 cancels out

x = 3
Answer 2
Answer: (3x+4)³=2197

3x+4=z

z³=2197
z=∛2197
z=13

Then:
3x+4=13
3x=13-4
3x=9
x=9/3
x=3

answer: x=3


Related Questions

-6x +6x-1 simplified
What is it called when two angles in a plane share a vertex and side but no common interior points?
What is the difference between 2,386 and 7,000? Check your answer using inverse operations.A. 5,614 B. 4,614 C. 9,386 D. 10,386
Is n=3 is a solution to the equation or 2n=6
Hey find the y intercept of the line 5x-4y=30

Help me with this problem please?Rewrite the equation with integer coefficients. Then, solve for x. Show all work.

4/5x+1/6=8/3x-2

New Equation:
x=

Answers

15(4/5 x + 1/6)=15(8/3 x-2)
12x + 2.5 = 40x - 30
12x - 12x +2.5 = 40x - 12x - 30
2.5 = 28x - 30
2.5 + 30 = 28x - 30 + 30
32.5 = 28x
32.5/28 = 28x/28
x=9/56


PLZZ HELP!!!!What is the surface area of the right rectangular prism?

Enter your answer in the box.

Answers

its 72 because i did lenght*whith*hight and got 72

Solve for x.
7x + 17 = 3x + 21

Answers

Answer:

x equals 1

combine the terms

.......................................................

Answers

For this problem, we only need the first term of the sequence to solve.

The first term of the sequence is represented by n = 1. Plug this into the equation:

-2 * 2^(1-1)
-2 * 2^(0) = -2 * 1 = -2

The only answer choice that has this result for their first term is -2; -16; -256.

M+4=-m+102x-2=x-4

5n-9=4n+2

5m-9=4m+2

-2x+3=-3x-1

7n+8=6n+4

m+3=-m-1

12m-5=11m-5

-3x+1=5x-7

5x-3=x-12

(I've been having trouble with these)

Answers

Question 1

M + 4  = -M + 10

First reorganize the terms on the left side

M + 4 = 10 - M

Take away 4 from both sides

M + 4 - 4 = 10 - M - 4
M = 10 - M - 4

Combine positive 10 and negative 4

M = 6 - M

Add M to both of the sides

M + M = 6 - M + M
M + M = 6
2M = 6

Divide both sides by 2

2M/2 = 6/2
M = 3

Question 2

2x - 2 = x - 4

Take away 1x from both sides of the equation

2x - 2 = x - 4
2x - 1x - 2 = x - 1x - 4
1x - 2 = -4
x - 2 = -4

Add 2 to both of the sides of the equation

x - 2 + 2 = -4 + 2
x = -2

Question 3

5n - 9 = 4n + 2

Add 9 to both sides of the equation

5n - 9 + 9 = 4n + 2 + 9
5n = 4n + 11

take away 4n from from both sides of the equation

5n - 4n = 4n - 4n + 11
5n - 4n = 11
1n = 11
n = 11

Question 4 
has the same values for question 3, they just changed n to a m

5m - 9 = 4m + 2
m = 11

Question 5

-2x + 3 = -3x - 1

Add 3x to both sides of the equation

-2x + 3x + 3 =  -3x + 3x - 1
1x + 3 = -1
x + 3 = -1

Take away 3 from both sides of the equation

x + 3 - 3 = -1 - 3
x = -4

Question 6
7n + 8 = 6n + 4

Take away 6n from both sides of the equation

7n - 6n + 8 = 6n - 6n + 4
1n + 8 = 4
n + 8 = 4

Take away 8 from both sides of the equation

n + 8 - 8 = 4 - 8
n = -4

Question 7

m + 3 = -m - 1

Add 1m to both sides of the equation

m + 1m + 3 = -m + 1m - 1
2m + 3 = -1

Take away 3 from both sides of the equation

2m + 3 - 3 = -1 - 3
2m = -4


I have 5 questions. <,>,or =. 67 miles____116,920 yards, 250 yards____800 feet, 14 yards and 2 feet_____16 feet, 34 feet 10 inches_____518 inches, 5 miles and 8 feet______8,800 yards. Please answer 3/5 of the questions

Answers

1 mile=1,760 yards
67 miles = 117,920 yards
that's > 116,920 yards

1 yard=3 feet
250 yards = 750 feet
that's < 800 feet

1 yard = 3 feet
14 yards = 42 feet
plus another 2 feet = 44 feet
that's much > 16 feet

1 foot = 12 inches
34 feet = 408 inches
plus another 10 inches = 418 inches
that's < 518 inches

1 mile = 1,760 yards
5 miles = 8,800 yards
that's already = to 8,800 yards, and we haven't even stuck the extra 8 feet on yet
when we do that, it'll be > 8,800 yards by exactly 8 feet (2 and 2/3 yards)